Development of time resolved x-ray spectroscopy in high intensity laser-plasma interactions - Notley, M; Weber, R; Fell, B; Jeffries, J; Freeman, R; Mackinnon, A; Dickson, R; Hey, D; Khattak, F; Saiz, E; Gregori, G (2006)
This article discusses the design of a novel time resolved von Hamos Bragg spectrometer to provide spectra in the region around the titanium K-alpha and He-alpha lines. The instrument consists of a highly oriented pyrolitic graphite mosaic crystal coupled to a picosecond x-ray streak camera. Measurements of the time dependent behavior from Ti foils illuminated with intense laser pulses can be used to improve the understanding of recombination dynamics, electron transport, and phase transitions in strongly coupled dense plasma. This is important for the modeling of the compression phase in inertial confinement fusion research and the study of astrophysical environments. (c) 2006 American Institute of Physics.